EFFECT OF DIETARY ASPIRIN ON PERFORMANCE AND HEALTH OF BROILERS REARED IN HIGH DENSITY: Faris A. Al-Obaidi , Shahrazad M. Al-Shadeedi , Ammar. T.D.AL-tememi - Al-Obaidi, Faris A. (The Iraqi Journal of Veterinary Medicine, 2009)
The objective of this study was to determine the effect of dietary aspirin on performance, healthstatus of broilers reared in high density (15 birds / m 0) . Ninety chicks 7 days old were distributed intotwo treatments , chicks in T1 fed a diet without aspirin (control) , chicks in T2 fed a diet supplementedwith 0.2 % aspirin . Each treatment was subdivided into three replicates and each replicate reared in 1X 1 m pen. Live body weight, weight gain , feed consumption , feed conversion ratio and mortality dueto ascites biweekly were recorded , also activity of some blood enzymes included GOT , GPT and ALPat 7 weeks of age . The data obtained revealed the following :Adding 0.2 % of aspirin in diet (T2) enhanced performance of broiler chicks compaired with control(T1) when reared in high density and the enhancement started at week 5 , dietary aspirin increased livebody weight , weight gain , feed conversion ratio and decreased total mortality and mortality due toascites , also dietary aspirin decreased ascites syndrome through decrease of liver and heart weightpercentages and decrease the activity of GOT and GPT at 7 weeks of age . Adding 0.2 % of aspirin inbroiler diet are recommanded to reduce crowding stress and ascites syndrome during high densityproduction.